Complement Factor H-Antibody–Associated Hemolytic Uremic Syndrome: Pathogenesis, Clinical Presentation, and Treatment - Hofer, Johannes; Giner, Thomas; Józsi, Mihály (Seminars in Thrombosis and Hemostasis, 2014)
The presence of circulating autoantibodies, primarily to complement factor H antibodies (CFH-Abs) in plasma characterizes the autoimmune form of atypical hemolytic uremic syndrome (aHUS). This acquired form of aHUS defines a distinct subgroup of aHUS patients, which requires diagnostic and treatment approaches in part different from those of the genetically defined forms. The mechanisms leading to CFH-Ab production and disease onset are not completely understood, but CFH-Ab HUS seems to be secondary to a combination of genetic predisposition and environmental factors. Early diagnosis of this specific aHUS entity is important, as prompt induction of plasma exchange and concomitant immunosuppression leads to a favorable outcome. Nevertheless, information on clinical features and outcome in children is limited. Here, we review the literature on the biological and clinical features of CFH-Ab HUS and discuss therapeutic options.
Keywords: complement factor H; complement factor H antibodies; atypical hemolytic uremic syndrome; complement-related diseases; transplantation